Adipose tissue and fat-derived products in wound, ulcer, and scar management: a systematic review - Sbitan, Lana; Qandah, Asem; Alzraikat, Noor; Camargo, Cristina P. (Frontiers in Surgery, 2025)
IntroductionAdipose-derived therapies hold promise in addressing the increasing prevalence of skin wounds, scars, and ulcers. This systematic review, conducted following the PRISMA guidelines, evaluates the therapeutic potential of adipose derived stem cells for improving wound healing, scar development and ulcer management.MethodsAn extensive search was conducted across PubMed, EMBASE, Scopus, Web of Science, Cochrane Central, and LILACS. The search strategy employed a combination of keywords and Medical Subject Headings (MeSH) terms related to “adipose tissue”, “fat derivatives”, “ulcers”, “wound healing”, and their synonyms, covering articles published from inception to October 2024. Our search yielded 589 records, with 16 randomized clinical trials and two ongoing studies meeting inclusion criteria after screening and full-text assessment.ResultsFindings indicate that adipose-derived therapies significantly enhance wound healing, reduce pain, and improve cosmetic appearance, patient satisfaction, and health-related quality of life compared to conventional treatments.DiscussionThese therapies demonstrate efficacy across various wound types and scars, with a favorable safety profile. However, further standardized protocols and large-scale randomized trials are essential to validate these outcomes and assess longterm safety. While adipose-derived therapies show promise in enhancing wound healing and managing scars, ongoing research is essential to facilitate their integration into routine clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024503209, PROSPERO CRD42024503209.